Experimental and numerical investigations of Q690D H-section columns under lateral cyclic loading. (June 2016) - Chen, Suwen; Chen, Xing; Wang, Yan-Bo; Lu, Zhili; Li, Guo-Qiang
Abstract: To evaluate hysteretic performance of welded Q690D high-strength steel H-section columns, cyclic loading test and numerical simulation were carried out. Firstly, cyclic loading test was performed on two H-section Q690D HSS welded columns with nominal axial compression ratio of 0.35. The observed failure mode is elastic–plastic local buckling of component plates. Hysteretic curves and skeleton curves of the test specimens show that the tested columns have a good energy dissipation capacity. Then, a finite element model was developed to simulate the hysteretic behavior of Q690D beam-columns and verified through comparison of numerical and experimental results. It is found that residual stresses are of ignorable influence on the ultimate bearing capacity of beam-columns. With the verified finite element model, extensive parametric analyses were conducted to investigate the effects of component plate slenderness ratio, column slenderness ratio and axial force ratio on the hysteretic performance of the Q690D H-section columns. Based on the observation and analyses of the experimental and numerical hysteretic curves, a trilinear moment-curvature hysteretic model for welded Q690D steel H-section column was proposed. Highlights: Hysteretic behavior of Q690D steel H-section column was experimentally evaluated. Extensive parametric analyses were conducted based on the verified numerical model. Effects of axial force ratio and geometrical dimensions were investigated. A trilinear hysteretic model for welded Q690D steel H-section column was proposed.